1988
DOI: 10.1080/00332747.1988.11024416
|View full text |Cite
|
Sign up to set email alerts
|

A Behavioral Perspective on Conduct Disorders

Abstract: THIS paper provides a selective overview of behavioral approaches for conduct-disordered behavior. Although no definitive statement can be made regarding etiology, some empirical support exists for behavioral strategies. Assessment approaches discussed include the behavioral interview, behavioral observations, and behavioral checklists. Decisions regarding types of behavioral interventions to be employed directly follow from assessment data. Assessment information can be formulated in terms of a behavioral exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
1992
1992

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Where approaches using the triadic model are successful, it is often unclear which modes of intervention or components of programmes are necessary or sufficient to promote change (Moreland et al, 1982;Webster-Stratton, 1985;Horton, 1987;Faulstich et al, 1988). In a review of the literature, O'Dell (1985) has suggested that the method of training accounts for only a small proportion of the outcome variance in changing parental knowledge and behaviour.…”
Section: Variations In Efficacy Dependent Upon Type Of Interventionmentioning
confidence: 96%
See 2 more Smart Citations
“…Where approaches using the triadic model are successful, it is often unclear which modes of intervention or components of programmes are necessary or sufficient to promote change (Moreland et al, 1982;Webster-Stratton, 1985;Horton, 1987;Faulstich et al, 1988). In a review of the literature, O'Dell (1985) has suggested that the method of training accounts for only a small proportion of the outcome variance in changing parental knowledge and behaviour.…”
Section: Variations In Efficacy Dependent Upon Type Of Interventionmentioning
confidence: 96%
“…Baumrind, 1978;Faulstich et al, 1988). Patterson (1982) has argued that "if they choose to, adults can set the level at which aggression will occur in young children" and that "training parents in child management skills is a necessary component for providing long-term changes in extremely antisocial children".…”
Section: Definition and Rationalementioning
confidence: 98%
See 1 more Smart Citation